European archaeology as anthropology : essays in memory of Bernard Wailes - Crabtree, Pam J.; Bogucki, Peter, 1954- (University of Pennsylvania Press, Inc., 2017)
Since the days of V. Gordon Childe, the study of the emergence of complex societies has been a central question in anthropological archaeology. However, archaeologists working in the Americanist tradition have drawn most of their models for the emergence of social complexity from research in the Middle East and Latin America. Bernard Wailes was a strong advocate for the importance of later prehistoric and early medieval Europe as an alternative model of sociopolitical evolution and trained generations of American archaeologists now active in European research from the Neolithic to the Middle Ages. Two centuries of excavation and research in Europe have produced one of the richest bodies of archaeological data anywhere in the world. The abundant data show that technological innovations such as metallurgy appeared very early, but urbanism and state formation are comparatively late developments. Key transformative process such as the spread of agriculture did not happen uniformly but rather at different rates in different regions. The essays in this volume celebrate the legacy of Bernard Wailes by highlighting the contribution of the European archaeological record to our understanding of the emergence of social complexity. They provide case studies in how ancient Europe can inform anthropological archaeology. Not only do they illuminate key research topics, they also invite archaeologists working in other parts of the world to consider comparisons to ancient Europe as they construct models for cultural development for their regions.